Recipe search engine using Yummly API - Malladi, Rajavardhan (Kansas State University, 2016)
In this project I have built a web application "Recipe Search Engine Using Yummly API". This application is central information hub for the kitchen--connecting consumers with recipe ideas, ingredient lists, and cooking instructions. It will serve best for the people who uses digital tools to plan their cooking, these days almost everyone does. The various features available for users in this application are as following. Users can search for their favorite dishes. The search results contain information about ingredients list, total time needed for cooking, user's rating and cooking directions. Basic search filters are provided to filter out the search results like Breakfast, Lunch and Dinner recipes. The order of displayed results can be sorted according to ratings, total time required to prepare the dish. User can create an account and build their own favorite recipe collection by liking the recipes displayed. The liked recipes are stored into user’s account and user can view, add and delete those recipes anytime from his recipe collection. Users can use their social networking platform Facebook account credentials to log into this application or create a new account in this application. The application will communicate with the Yummly API to consume data from it. The Yummly API is largest recipe information aggregator with over one million recipes data.
Keywords: Web Services; Yummly API; Recipe Search engine; ASP.NET C#; Entity Framework